Dissecting Monomer-Dimer Equilibrium of an RNase P Protein Provides Insight Into the Synergistic Flexibility of 5’ Leader Pre-tRNA Recognition - Zeng, Danyun; Abzhanova, Ainur; Brown, Benjamin P.; Reiter, Nicholas J. (Frontiers in Molecular Biosciences, 2021)
Ribonuclease P (RNase P) is a universal RNA-protein endonuclease that catalyzes 5’ precursor-tRNA (ptRNA) processing. The RNase P RNA plays the catalytic role in ptRNA processing; however, the RNase P protein is required for catalysis in vivo and interacts with the 5’ leader sequence. A single P RNA and protein form the functional RNase P holoenzyme yet dimeric forms of bacterial RNase P can interact with non-tRNA substrates. Oligomeric forms of the P protein can also occur in vitro and occlude the 5’ leader ptRNA binding interface, presenting a challenge in defining the substrate recognition properties. To overcome this, concentration and temperature dependent NMR studies were performed on an RNase P protein from Thermatoga maritima. NMR relaxation (R1, R2), heteronuclear NOE, and diffusion ordered spectroscopy (DOSY) studies identified a monomeric species through the determination of the diffusion coefficients (D) and rotational correlation times (tau c). Diffusion coefficients and tau c values for the predominant monomer (2.17 ± 0.36 * 10-10 m2/s, tau c = 5.3 ns) or dimer (1.87 ± 0.40 * 10-10 m2/s, tau c = 9.7 ns) conformers at 45 oC correlate well with calculated diffusion coefficients from the crystallographic P protein (PDB 1NZ0). The identification of a monomeric P protein from relaxation data and chemical shift information enabled us to gain insight into the P protein structure, highlighting a lack of structural convergence of the N-terminus (residues 1-14). We propose that the N-terminus of the P protein is partially disordered and adopts a stable conformation in the presence of RNA. In addition, we determined the location of the 5’ leader RNA in solution and measured the affinity of the 5’ leader RNA - P protein interaction. The monomeric P protein interacts with RNA at the 5’ leader binding cleft that was previously identified using X-ray crystallography. Data support a model where N-terminal flexibility is stabilized by holoenzyme formation and helps to accommodate the 5’ leader region of ptRNA. Taken together, local structural changes of the protein and the 5' leader RNA provide a means to obtain optimal substrate alignment and activation of the RNase P holoenzyme.